Extraction of Essential Oils of Lemon Grass Using Ionic Liquid - Murata, Chihiro; Yoshizawa-Fujita, Masahiro; Rikukawa, Masahiro; Usuki, Toyonobu (Asian Journal of Chemistry, 2016)
Geranial [(E)-3,7-dimethyl-2,6-octadienal], neral [(Z)-3,7-dimethyl-2,6-octadienal] and geraniol [(E)-3,7-dimethyl-2,6-octadien-1-ol] are found in lemon grass and are attractive essential oils with potential medicinal applications. In this study, a new method for extracting these natural flavour substances from lemon grass using co-solvent systems consisting of methanol or ethyl acetate and the ionic liquids 1-butyl-3-methylimidazolium chloride ([C4mim]Cl) or 1-ethyl-3-methylimidazolium methylphosphonate ([C2mim][(MeO)(H)PO2]) is described.